1994
DOI: 10.1291/hypres.17.105
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Regulation of Aldosterone Secretion in Primary Aldosteronism: A Clinical Study.

Abstract: To assess the role of dopaminergic inhibition of aldosterone secretion in primary aldosteronism (PA) we studied the effect of dopaminergic DA2 blockade and stimulation in a series of consecutive cases of PA, and of primary hypertension (PH) as controls. Thirteen patients with confirmed PA (11 adenoma, 2 idiopathic hyperaldosteronism) and 8 primary hypertensive subjects (PH) were studied while on a 100 mmol/day sodium diet. Patients with aldosterone-producing adenoma were studied before, 1-2 wk after, and 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…It is noteworthy that this study by showing that metoclopramide increased the plasma adrenal vein level of aldosterone demonstrates that this hormone is under tonic dopaminergic D 2 receptormediated inhibition and confirms previous limited observations (7). Whether this could improve the lateralization of excessive aldosterone to the affected side, and thereby the diagnosis of the surgically curable subtypes of PA, is currently being pursued in a large prospective study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is noteworthy that this study by showing that metoclopramide increased the plasma adrenal vein level of aldosterone demonstrates that this hormone is under tonic dopaminergic D 2 receptormediated inhibition and confirms previous limited observations (7). Whether this could improve the lateralization of excessive aldosterone to the affected side, and thereby the diagnosis of the surgically curable subtypes of PA, is currently being pursued in a large prospective study.…”
Section: Discussionsupporting
confidence: 86%
“…Dopamine is held to tonically inhibit aldosterone secretion because the selective D 2 receptor antagonist metoclopramide induces aldosterone release in humans (6,7). More recent evidence showed that the dopamine acts by blunting Ca 2C influx and protein kinase C phosphorylation (8), which suggests that its inhibitory effect involves the early steps of the steroidogenesis and therefore are not confined to aldosterone synthesis, but may involve also cortisol and its precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Several stimuli, including the 4-hour upright posture test, volume expansion procedures, infusion of angiotensin (Ang) II and corticotropin (ACTH), and administration of captopril, losartan, and dopaminergic (dopamine, DA 2 ) receptor agonists and antagonists [16] have, therefore, been exploited to functionally differentiate cases that can be cured by adrenalectomy from cases that cannot [17]. However, results of these procedures have been disappointing in differentiating between APA and IHA.…”
Section: Demonstration Of the Autonomous Nature Of Aldosterone Excessmentioning
confidence: 99%